158k views
4 votes
Solve the equation algebraically. Support your answer numerically and identify any extraneous solution

4.)

(1)/(x) - (2)/(x - 3) = 4

User Haynes
by
5.2k points

1 Answer

5 votes

1/x - 2/(x-3) = 4

multiply each side by x*(x-3)

x*(x-3)(1/x - 2/(x-3)) = 4*x*(x-3)

distribute

x*(x-3)(1/x) - 2/(x-3))x*(x-3) = 4*x*(x-3)

cancel

(x-3) - 2*x = 4x(x-3)

distribute

x-3-2x = 4x^2-12x

combine like terms

-x-3 = 4x^2 -12x

add x+3 to each side

0 = 4x^2 -12x+x+3

0 = 4x^2 -11x+3

using the quadratic formula

x= 11/8 - sqrt (73)/8

x=11/8 + sqrt (73)/8

User Joey T
by
5.1k points